2007
DOI: 10.1093/fampra/cmm070
|View full text |Cite
|
Sign up to set email alerts
|

Improving prevention in primary care: evaluating the effectiveness of outreach facilitation

Abstract: ing prevention in primary care: evaluating the effectiveness of outreach facilitation. Family Practice 2008; 25: 40-48. Background. Out reach facilitation is designed to promote uptake of evidence-based guidelines. There is evidence indicating that outreach facilitation can be effective in improving implementation of preventive care in GPs' offices. In this trial, we test a modified version of an outreach facilitation intervention.Objective. To evaluate whether a comprehensive preventive intervention program u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 12 publications
0
65
1
Order By: Relevance
“…16 For each patient, we calculated an overall prevention score by dividing the number of manoeuvres performed by the number of manoeuvres for which the patient was eligible within the previous 24 months and then multiplying by 100. For example, for a 55-year-old woman eligible for the three cancer screening manoeuvres, her score would be based on the number of cancer screening manoeuvres performed divided by three and multiplied by 100.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…16 For each patient, we calculated an overall prevention score by dividing the number of manoeuvres performed by the number of manoeuvres for which the patient was eligible within the previous 24 months and then multiplying by 100. For example, for a 55-year-old woman eligible for the three cancer screening manoeuvres, her score would be based on the number of cancer screening manoeuvres performed divided by three and multiplied by 100.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…6-9 Furthermore, leadership, 10 practice facilitation, 11 and organizational adaptive reserve 12-14 modify a practice's ability to transform. To begin to test large-scale interventions to transform practices, however, a more specifi c description of the process of transformation is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that offi ce systems changes are necessary for quality improvement (QI) [1][2][3][4][5] and implementation of the patient-centered medical home (PCMH). [6][7][8][9] Furthermore, leadership, 10 practice facilitation, 11 and organizational adaptive reserve 12-14 modify a practice's ability to transform. To begin to test large-scale interventions to transform practices, however, a more specifi c description of the process of transformation is necessary.…”
mentioning
confidence: 99%
“…17 Another meta-analytic review found practices receiving PF were three times as likely as control practices to implement guidelines. 18 Studies also found the effects from PF to be sustained for as long as 12 months postintervention, [19][20][21][22] with evidence of costeffectiveness. 23 However, it remains unknown whether the effects of PF focused on using QI methods impacts clinical process measures in rural clinics caring for patients with chronic pain.…”
mentioning
confidence: 99%